Healthcare workers’ attitudes and practices around environmental sustainability in infection prevention - Ashley L. Lin; Michelle E. Doll; Rachel J. Pryor; Elizabeth A. Monsees; Priya Nori; Gonzalo M. Bearman (Antimicrobial Stewardship & Healthcare Epidemiology)
We assessed healthcare workers’ knowledge, attitudes, and practices around disposable personal protective equipment (PPE) use. We observed that healthcare workers are interested in sustainable policies and identified areas for policy changes to reduce PPE waste.